Effect of curcumin-lipiodol emulsion combined with absorbable anti-adhesion film through double embolic pathway on angiogenesis and overall survival (OS) time of VX2 liver cancer rabbits - Yang, Chuanyu; Xu, Zheng; Nie, Kai; Liu, Jing (Translational Cancer Research; Vol 9, No 2 (February 28, 2020): Translational Cancer Research, 2019)
Background: Curcumin is a promising anti-tumor drug in recent years. The main function of absorbable anti-adhesion film is to prevent adhesions after surgical operation. The effects of curcumin-lipiodol emulsion injected via the hepatic artery and portal vein catheter combined with using absorbable anti-adhesion film around the liver angiogenesis are unknown. This article mainly discusses the effects of these combined strategies on the inhibition or reduction of postoperative angiogenesis and prolonging survival time of rabbit model. Methods: Forty model rabbits with VX2 liver cancer were divided into four groups. Group A is the control group and its intervention is a simple lipiodol emulsion group. The intervention in group B was a simple lipiodol emulsion combined with an anti-adhesion membrane. The intervention in group C was a mixture of curcumin and lipiodol. The intervention in group D was a mixed emulsion of curcumin and lipiodol combined with an anti-adhesion membrane. The levels of aspartate aminotransferase (ALT) and alanine aminotransferase (AST) in the model rabbits were compared to analyze the damage of liver cells 1 day before embolization and 3, 7, 14 days after the embolization. In addition, the levels of vascular endothelial growth factor (VEGF) and microvessel density (MVD) in residual cancer tissues were determined by immunohistochemistry and Western blot. Finally, overall survival time (OS) of each group was recorded. Results: The results showed that the ALT and AST levels of venous blood before and after embolization in each group of rabbits were not changed significantly (P>0.05). The levels of VEGF and MVD in the group C and group D were lower than those in the group A (P0.05). The decrease of VEGF and MVD in group D was most obvious, and group D had a significant difference compared with group C (P0.05). The OS time of group C and group D was longer than that of group A (P